2021
DOI: 10.1016/j.ejrad.2020.109478
|View full text |Cite
|
Sign up to set email alerts
|

Value of minimum intensity projections for chest CT in COVID-19 patients

Abstract: To investigate whether minimum intensity projection (MinIP) reconstructions enable more accurate depiction of pulmonary ground-glass opacity (GGO) compared to standard transverse sections and multiplanar reformat (MPR) series in patients with suspected coronavirus disease 2019 . Method: In this multinational study, chest CT scans of 185 patients were retrospectively analyzed. Diagnostic accuracy, diagnostic confidence, image quality regarding the assessment of GGO, as well as subjective timeefficiency of MinIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The next commonest radiological finding was ground glass attenuation seen in 8 patients in 2020, and 7 patients in 2021. Christian Booz et al reported in a recent study that minimum intensity projection chest CT reconstructions demonstrate ground glass attenuation better than standard CT scan axial and multiplanar image reformats [ 23 ]. Tables 2 and 3 shows that more than half of the patients in each group presented with bilateral lung involvement, 29 (58%) and 37 (74%) in the 2020 and 2021 groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The next commonest radiological finding was ground glass attenuation seen in 8 patients in 2020, and 7 patients in 2021. Christian Booz et al reported in a recent study that minimum intensity projection chest CT reconstructions demonstrate ground glass attenuation better than standard CT scan axial and multiplanar image reformats [ 23 ]. Tables 2 and 3 shows that more than half of the patients in each group presented with bilateral lung involvement, 29 (58%) and 37 (74%) in the 2020 and 2021 groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CXR and CT are crucial for diagnosis and typical signs of tension include mediastinal shift, displacement of anterior junction line, azygoesophageal recess, and flattening of heart [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the reference standard for diagnosis is real-time reverse-transcription polymerase chain reaction (rt-PCR) test applied on respiratory tract specimens, chest multidetector computed tomography (CT) may help in the early detection, management, and follow-up of COVID-19 pneumonia [ 5 9 ]. Typical CT features of COVID-19 pneumonia include bilateral ground glass opacities with a predominant posterior and peripheral distribution, parenchymal consolidations with or without air bronchogram, interlobular septal thickening and crazy paving pattern, usually without pleural effusion or enlarged mediastinal lymph nodes [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%